Análise semiótica de discursos discentes de Institutos Federais Nordestinos - Barbosa, Arlindo Lopes (2010)
This Thesis of Doctorate is the result of the semiotic analysis of some speeches of experienced and inexperienced pupils of technical courses integrated of the secondary education of the Federal Institutes (FIs) situated in the following cities, in the Northeast region of the Brazil: Aracaju, Fortaleza, João Pessoa, Maceió, Natal, Recife, Salvador, São Luís and Teresina. In these speeches, we identified and analyzed the marks of the enunciation and, by means of them, the values or the hypotheses raised for the related pupils about the Federal Institutes where they were studying. Questionnaires had been applied to harvest information about the quality of the education given in each FI, in the spring semester of 2008. Of the questionnaires voluntarily returned, we select fifteen to represent the answers of each group of pupils, being totalized thirty in each Institute, which constituted in the corpus of this work. To base our work of research, we invoke the French semiotics of Greimas‟ inspiration (1966, 1970, 1976, 1979) whose objective is to explain the generation and the signification of the speeches , complemented by the ideas of the semio-linguistics of Charaudeau (2007 and 2008) and of the tensive semiotics of Zilberberg (1992 and 1997) and of Fontanille (2007). The result of this analysis permitted us to check that speeches both show similar values, beliefs and hypotheses about the Institutes where the pupils were studying, with differences only of the assessment percentages. In general, the inexperienced pupils are more generous than the experienced pupils in the all Institutes, with high percentages of the positive assessment; but the experienced pupils are stricter than inexperienced pupils and assessed negatively three Institutes where they were studying.